The Exercise of the Spatial Imagination in Pre-Modern China Shaping the Expanse - Pagenstecher Olberding, Garret (Welten Ostasiens / Worlds of East Asia / Mondes de l'Extrême Orient, 2022)
This volume is distinctive for its extraordinarily interdisciplinary investigations into a little discussed topic, the spatial imagination. It probes the exercise of the spatial imagination in pre-modern China across five general areas: pictorial representation, literary description, cartographic mappings, and the intertwining of heavenly and earthly space.